1999
DOI: 10.3109/08923979909007125
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Nonspecific Immunity and Plasma Levels of Interferon-γ, Interleukin-6 and Tumor Necrosis Factor-α in Preeclampsia

Abstract: In this study we evaluated the maternal cell-mediated immune aspects of preeclampsia in terms of phagocytosis and killing of monocytes and polymorphonuclear cells. To evaluate the contribution of cytokines (Cks) in the pathophysiology of preeclampsia, we investigated the plasma levels of interferon-gamma (IFN-gamma), interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-alpha), respectively, by an enzyme-linked immunosorbent assay. Data showed that phagocytic and killing activities of monocytes were depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 19 publications
1
19
1
Order By: Relevance
“…Contrary to many other studies (Munno et al, 1999;Omu et al, 1999), we found no evidence that the circulating marker of immune activation, TNF-a, is significantly increased in the serum of women with preeclampsia compared with normal pregnancy. Our results, however, are consistent with the findings of Moodley and Devjee (1998) and Heyl et al (1999).…”
Section: Discussioncontrasting
confidence: 85%
“…Contrary to many other studies (Munno et al, 1999;Omu et al, 1999), we found no evidence that the circulating marker of immune activation, TNF-a, is significantly increased in the serum of women with preeclampsia compared with normal pregnancy. Our results, however, are consistent with the findings of Moodley and Devjee (1998) and Heyl et al (1999).…”
Section: Discussioncontrasting
confidence: 85%
“…There are studies indicating a consistent increase in TNF-a production, 39 others reporting that a part of these patients exhibit Table 2 Genotype frequencies of the TNF-a promoter (À308 G4A), IL6 promoter (À174 G4C), IFN-c intron 1 (+874 A4T), IL10 promoter (À1082 A4G), (À819 C4T), (À592 C4A) and TGF-b1 codon 10 (+869 T4C), codon 25 (+915 G4C) polymorphisms in women with preeclampsia, eclampsia and controls a high TNF levels, 40 whereas some investigators did not detect any change in cytokine levels. 41 These discrepancies have been reported for almost all cytokines. 42 These several conflicting findings could be because of heterogeneity in study designs, definition of phenotype, SNP selection, population diversity and sample size.…”
Section: Discussionmentioning
confidence: 93%
“…41,43,48,49 . As the present study was undertaken in women with established pre-eclampsia, it is not possible to determine whether the altered cytokine levels represent a cause or consequence of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…For individual cytokines, we observed increased TNF-a and IL-6 and reduced IL-10 in the combined pre-eclampsia cohort compared with matched normal pregnancy controls; these are consistent with other published reports. [40][41][42][43][44][45][46] The imbalance between inflammatory and anti-inflammatory cytokines probably contributes to endothelial dysfunction, 47 and is therefore linked with the pathogenesis of preeclampsia…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation